Strategi pembelajaran kontekstual untuk meningkatkan literasi sosial siswa kelas 3 sd pada materi ipas - Rahma Tsani Azalia; Joko Suprapmanto (Universitas Sebelas Maret, 2026)
Contextual Teaching and Learning (CTL); Elementary School; IPAS; Social Literacy.This study aimed to analyze the effect of the Contextual Teaching and Learning (CTL) strategy on improving the social literacy of third-grade elementary school students in Integrated Science and Social Studies (IPAS) learning. The study was motivated by students' low level of social literacy, particularly in connecting learning materials with real-life social contexts, collaborating with peers, and understanding social situations in their surrounding environment. This research employed a quantitative approach using a quasi-experimental design. The research participants consisted of third-grade students from SDN Bojongkawung as the experimental class and SDN Babakan Cibatu as the control class in the Cisaat Gadis Cluster, Sukabumi Regency. Data were collected through a social literacy questionnaire, observation, and documentation, while data analysis included validity testing, reliability testing, normality testing, homogeneity testing, and Welch's Test. The results showed that the mean social literacy score of the experimental class increased from 57.17 in the pretest to 71.56 in the posttest, whereas the control class showed only a slight increase from 55.00 to 56.52. The hypothesis testing using Welch's Test produced a significance value of 0.001 (< 0.05), indicating that the Contextual Teaching and Learning strategy had a statistically significant effect on improving the social literacy of third-grade elementary school students in IPAS learning. These findings indicate that the CTL strategy provides meaningful learning experiences by connecting learning materials with real-life situations, thereby enhancing students' ability to interact, collaborate, and understand various social situations. The findings are expected to serve as a reference for teachers in implementing contextual learning strategies to improve students' social literacy in elementary school IPAS learning..